2011
DOI: 10.1007/s11069-011-9758-z
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial contour mapping of shear wave velocity for Mumbai city

Abstract: Shear wave velocity is one of the most important input parameter in the analysis of geotechnical earthquake engineering problems, particularly to estimate sitespecific amplification factor and ground response study. Dynamic in situ tests such as spectral analysis of surface waves (SASW) or multichannel analysis of surface waves (MASW) are very expensive. Also due to lack of specialized personnel, these tests are generally avoided in many soil investigation programs. Worldwide, several researchers have develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Maheswari et al (2010) [4] reported that the corrected and uncorrected N values predicted V s with equal accuracy. Mhaske and Choudhury (2011) [15] also concluded that correlation of uncorrected SPT N value and shear wave velocity V s can give reasonably good estimate of value of shear wave velocity for typical soil of Mumbai city. In view of this, shear wave velocity is determined from the uncorrected N values.…”
Section: Shear Wave Velocity Based On N Valuementioning
confidence: 96%
“…Maheswari et al (2010) [4] reported that the corrected and uncorrected N values predicted V s with equal accuracy. Mhaske and Choudhury (2011) [15] also concluded that correlation of uncorrected SPT N value and shear wave velocity V s can give reasonably good estimate of value of shear wave velocity for typical soil of Mumbai city. In view of this, shear wave velocity is determined from the uncorrected N values.…”
Section: Shear Wave Velocity Based On N Valuementioning
confidence: 96%
“…Furthermore, in the USA, similar studies investigating the correlation between Vs and N30 showed that corrected SPT-N values yielded better correlations compared with the uncorrected SPT-N values [21]. In Japan, a great number of researchers developed correlations between the SPT-N and Vs values by taking the geological age and soil type into account.…”
Section: Maswmentioning
confidence: 99%
“…Model B consists of 6 layers above bedrock. The shear wave velocity 'V s ' is estimated by using available correlations with SPT N values developed by Fujiwara (1972), Imai et al (1975), Imai and Tonouchi (1982), Mhaske and Choudhury (2011), Chatterjee and Choudhury (2013). The two models differ in the shear wave velocity profile.…”
Section: Soil Geometry Models Considered For the Present Studymentioning
confidence: 99%